The Effectiveness of Blended Learning Model for Teaching Vocabulary at Secondary School - Gusnita Gusnita; Kisman Salija; Haryanto Atmowardoyo (Celebes Journal of Language Studies, 2021)
The present study applies Blended learning model to secondary school level and conduct experimental study of 36 students of eleventh grade. Eighteen students in experimental group received blended learning model by application of supporting tools of visuwords, while in control group students were taught with face-to-face learning model. The purpose of this study was (1) to analyze the effectiveness of blended learning model in improving students’ vocabulary achievement, and (2) to elaborate how students perceive blended learning. The research revealed that both experimental class and Control class were improved in vocabulary achievement based on the given context. The effectiveness of Blended learning model was medium. However, the experimental class vocabulary improvement was greater than Control class. Moreover; the students dominantly had positive perception on the blended learning model. That perception is proven on their feelings which are happy on blended learning model and their thinking that their score influence their score. Therefore, was concluded that the use of a Blended learning model affect the learners’ achievement. Moreover, Students' perceptions were positive and confirm the perception was in line with the students’ grade in vocabulary achievement.